Lag Synchronization of a Class of Time-delayed Chaotic Neural Networks by Impulsive Control - Jing Wan; Jianliang Ai (Institute of Advanced Engineering and Science, 2013)
The paper studies the exponential lag synchronization of a class of delayed chaotic neural networks with impulsive effects via the unidirectional linear coupling. Some sufficient conditions are derived by establishing impulsive differential delay inequality and using M-matrix theory. An illustrative example is also provided to show the effectiveness and feasibility of the impulsive control method. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2692